(untitled) (Journal of NELTA, 2010)
Writing requires mastery on its basic components to make it an effective piece of discourse. It can be taught so easily that the students keep on improving and getting motivation to write much more if we follow the proper approach of teaching writing. This article attempts to highlight the basic literacy about the components and approaches of developing writing, and focuses on the model text deconstruction process (MTDP) of teaching writing. The experiment made during the competency based training laid foundation for this article. Key words: Model Text Deconstruction Process (MTDP); academic writing; analyzing writing DOI: 10.3126/nelta.v14i1.3086 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 14-20